2018
DOI: 10.1002/lary.27564
|View full text |Cite
|
Sign up to set email alerts
|

Dexpramipexole depletes blood and tissue eosinophils in nasal polyps with no change in polyp size

Abstract: Objective Chronic rhinosinusitis with nasal polyps (CRSwNP) and eosinophilia is a disease of the upper respiratory tract for which few therapies are available. Because the oral investigational drug dexpramipexole serendipitously decreased blood eosinophils in amyotrophic lateral sclerosis studies, we assessed its safety, eosinophil‐lowering activity, and preliminary clinical efficacy in patients with CRSwNP and eosinophilia. Methods Sixteen subjects with CRSwNP, absolute eosinophil count (AEC) ≥ 0.300 × 109/L,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 27 publications
5
60
0
Order By: Relevance
“…47 However, another recent study of dexpramipexole, an experimental drug that depletes nearly all eosinophils from within the nasal polyp tissue, failed to show any symptomatic improvement or any reduction in nasal polyp size. 48 Taken together with our current findings, we suspect that IL-5targeting monoclonal antibodies may alter the survival and function of IL-5Rα + antibodysecreting cells, which may contribute to the mechanism of their therapeutic benefit. IgG and IgA isotype heavy chain regions (IGHG1, IGHG2, IGHG3, IGHG4, IGHA1, IGHA2), (D) the immunoglobulin E heavy chain (IGHE), and (E) the IL-5 receptor alpha chain (IL5RA).…”
Section: Discussionsupporting
confidence: 77%
“…47 However, another recent study of dexpramipexole, an experimental drug that depletes nearly all eosinophils from within the nasal polyp tissue, failed to show any symptomatic improvement or any reduction in nasal polyp size. 48 Taken together with our current findings, we suspect that IL-5targeting monoclonal antibodies may alter the survival and function of IL-5Rα + antibodysecreting cells, which may contribute to the mechanism of their therapeutic benefit. IgG and IgA isotype heavy chain regions (IGHG1, IGHG2, IGHG3, IGHG4, IGHA1, IGHA2), (D) the immunoglobulin E heavy chain (IGHE), and (E) the IL-5 receptor alpha chain (IL5RA).…”
Section: Discussionsupporting
confidence: 77%
“…38 Interestingly, there are some contradictory studies and doubts on the role of eosinophils, which may need further explanation. 64,65 However, mepolizumab, reslizumab, and benralizumab reduce blood and tissue eosinophil counts, reduce corticosteroid dependence and asthma exacerbations, and are approved for the treatment of severe eosinophilic asthma. [66][67][68] Their effectiveness also has been demonstrated for CRSwNP, with mepoliumab and benralizumab currently in phase 3 trials.…”
Section: Antagonizing Eosinophil Activation In Crswnpmentioning
confidence: 99%
“…However, we may need to resist the impulse to then assume that eosinophils themselves should be directly targeted with therapeutics, because anti-eosinophil trials have not shown great success for CRSwNP. 31,32 Interestingly, immunoglobulin levels are also globally increased within nasal polyp tissue, including IgE and autoantibodies of all isotypes. 30,[33][34][35] Furthermore, although plasma IgE levels are also increased in patients with CRSwNP, there is no association of these IgE levels with the presence of atopy or environmental allergies.…”
Section: Biomarker Classification: Cells Cytokines and Antibodiesmentioning
confidence: 99%